The genus Anarsia in Cambodia and the Northern Vietnam (Lepidoptera, Gelechiidae), with descriptions of ten new species and a catalogue of the genus in the Central-East Asia - Bae, Yang-Seop; Shin, Young-Min; Na, Sol-Moon; Park, Kyu-Tek (Zootaxa, 2016)
The genus Anarsia Zeller in Vietnam and Cambodia is reviewed, with 19 species including 10 new species: A. deuterodes Park, sp. nov., Anarsia diversiola Park, sp. nov., A. porthmista Park, sp. nov., A. melanodes Park, sp. nov., A. gryphodes Park, sp. nov., A. campestra Park, sp. nov., A. similicampa Park, sp. nov., A. kepensis Park, sp. nov., A. pusillidia Park, sp. nov., and A. houhunlii Park, sp. nov. Nine previously described species, namely A. tricornis Meyrick, A. choana Park, A. isogona Meyrick, A. paraisogona Meyrick, A. incerta Ueda, A. acerata Meyrick, A. didymopa Meyrick, A. phortica Meyrick, and A. patulella (Walker), are reported for the first time from Vietnam or Cambodia. Anarsia magnibimaculata Li & Zheng, 1998 is newly synonymized with A. bimaculata Ponomarenko, 1989. A tentative check list of the genus in the Central and East Asia (including Indochina, China, Russian Far East, Korea, and Japan) is given.